ID 333 – Neurophysiological responses of pain facial expressions: an intracerebral electrophysiologic study. Issue 3 (March 2016) - Czekala, C.; Mauguière, F.; Garcia-Larrea, L.; Frot, M.
Abstract : Pain facial expressions have important communicative values as they could indicate a potential dangerous situation. Thus, they should be detected rapidly. In this study, we investigated the cerebral network that could trigger this alarm signal in reaction to pain facial expressions. Nine epileptic patients with deep electrodes implanted after brain surgery were recorded when their attention were shifted away (implicit condition) or focused (explicit condition) to the emotional aspect of faces presented for 400 ms. Event-related potentials (ERP) of neutral faces were compared with ERP of pain faces, in the 800 ms after stimuli onset, in regions constituting the pain matrix, i.e. the cortical network responding to nociceptive stimuli. In the implicit condition, responses within the anterior insula had higher amplitudes for pain than for neutral faces, starting at ∼160 ms after stimuli onset, while such differences were not found neither in the sensory (posterior) insula nor in frontal high-order areas (BA 47). ERP of the anterior insula did not differ in amplitude or latency in the explicit condition. This result is in line with the role of anterior insula as interface between sensory processing and subjective feelings and shows its preponderant role in the implicit recognition of pain faces.